Bacillus licheniformis a potential bio-collector for Barite-Quartz selective separation. (1st January 2022) - Abedi Ashkavandi, Rasool; Azimi, Ebrahim; Hosseini, Mohammad Raouf
Highlights: Bacillus licheniformis cells enhanced barite hydrophobicity, as a bio-collector. Selective cell-assisted flotation of barite from a mixed sample was obtained. Cell adsorption density on barite and quartz particles was attained. Effects of parameters on adsorption and selective separation were determined. Adsorption of bacterial cells on both minerals was modeled using kinetics models. Abstract: Employing microorganisms and their metabolites as a potentially low-cost and environmentally friendly alternative for the synthetic compounds in many of the current mineral beneficiation techniques is receiving increasing attention. For the first time, the influence of the Bacillus licheniformis cells and its metabolites for selective flotation of barite from quartz was studied. The maximum adsorption density of 1.33 × 10 10 cells/g was achieved at pH = 3 for barite, six times higher than quartz. Flotation experiments revealed that cell-assisted separation was more effective than metabolite-facilitated flotation, either for single mineral or the mixed sample (barite mixed with quartz). Barite was recovered up to 87% (at pH = 3) in sole-mineral flotation experiments, and flotation of the mixed sample, also, proved a successful selective separation of barite (76% recovery) from quartz at the bio-collector dosage of 6.55 × 10 3 cells/ml. Adsorption kinetics study showed that the pseudo second-order model could represent cell adsorption densities for both minerals, while the Langmuir model simulated adsorption isotherms. Finally, it was shown that B. licheniformis cells could selectively enhance particles hydrophobicity and successfully be utilized as a bio-collector.